Lijst van monialen in het Norbertinessenklooster van Sint-Gerlach te Houthem, circa 1202-1600 - Notten, Jan G.M.; Heijnens, Fons (Heemkundevereniging Houthem-St. Gerlach, 2006)
Keywords: sint-gerlach

Toon mij Uw schoenen en ik zal zeggen wie gij zijt - Emmen, L. C. J.; Krikke, D. (Archeologie in Limburg: Uitgave van de Archeologische vereniging Limburg, 2000)
Discusses leather finds from a cesspit of the Premonstratensian nunnery of Sint-Gerlach in Houthem excavated in 1993-1996, including a girdle for a sword datable to 1340-1370 and fragments of several types of shoes
Keywords: sint-gerlach